Phytochemical, fatty acid and proximal composition of six selected Indonesian brown rice varieties - Hadi Munarko; Azis Boing Sitanggang; Feri Kusnandar; Slamet Budijanto (CyTA - Journal of Food, 2020)
Within this study, phytochemical, fatty acid and proximal composition of six Indonesian brown rice cultivars (Inpari 42, Inpari 43, Situ Bagendit, IPB3 S, Inpari 17, and Inpara 3) were reported. The range of moisture, ash, crude fat, crude protein, and total carbohydrates content of six varieties of brown rice were 11–12%, 1.3–1.4%, 2–3%, 7–11%, and 84–89%, respectively. Fatty acid composition of brown rices was dominated by unsaturated fatty acids. The phenolic contents and IC50 of all cultivars varied from 47 to 70 mg GAE/100 g and 28–47 mg/mL, respectively. Inpari 17 had the highest phenolic content as well as antioxidant activity, whereas IPB 3 S variety exhibited the lowest in both γ-oryzanol content of brown rices ranged from 37 to 55 mg/100 g. The highest content of γ-oryzanol was observed in Inpara 3. In conclusion, six varieties of Indonesian brow rice might be considered as the potent sources of bioactive compounds and antioxidant, especially in Inpari 17 variety.